Violet Balestreri Archer: Milestones of a Career (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
Un article de la revue Canadian University Music Review / Revue de musique des universités canadiennes, diffusée par la plateforme Érudit.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Musica E Poesia Nell’ Opera di Violet Archer [Musique et poésie dans l'œuvre de Violet Archer] - Calo, Francesca (Université de Rome « La Sapienza », 1995)
Keywords: Pas de lien web

Women's Roles in Judeo-Spanish Song Traditions - Cohen, Judith R.; Sacks, Maurie (Active Voices: Women in Jewish Culture, 1995)

The Composer's Voice: "What women can do" - Dalen, Brenda (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
In this interview, conducted on 18 August 1994, Violet Balestreri Archer revisits her past, recreating the experiences of her youth from the earliest days of her childhood in Como and Montreal to her graduation from Yale University in 1949 and sharing highly personal memories of her family, teachers, and friends. She recalls her first visit to Italy, her school years, her piano lessons, her early attempts at composition, her participation in the Montreal Women's Symphony, and her compositional studies with Douglas Clarke at McGill University, Béla Bartók in New York, and Paul Hindemith at Yale University. In listening to her story, we discover "who" she is and "how" she succeeded in establishing her compositional voice and in creating a space or "room" for herself in a profession traditionally dominated by men.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Sacred songs and arias by women composers: A survey of the literature and performer's analysis of selected works by Isabella Leonarda, Luise Reichardt, Ethel Smyth, Violet Archer, Margaret Bonds and Edith Borroff - Heape, Mary Willis (Séminaire théologique baptiste du Sud-Ouest, 1995)
This document is written in support of a recital of sacred songs and arias by women composers. It is divided into two sections: a survey of sacred music, specifically sacred arts songs and sacred arias from larger works, and a performer's analysis of selected works drawn from the research of the first part. The survey begins with the commercial printing of music around 1500 and extends to 1994. Countries from around the world are represented, some more broadly than others. Biographical information, when available, is given for each composer featured in the survey as well as some discussion of her general compositional style and output. Greater attention is given to the composer's sacred music, especially compositions that involve the solo voice. Composers who wrote very little sacred music for the solo voice are mentioned only briefly. The performer's analysis includes biographical information on each composer as well as a discussion of her general style, significant compositions, honors and awards and sphere of influence. In the analysis of the pieces, attention is focused on elements in the music that affect its performance. The selected works include Volo Jesum, a solo motet by Isabella Leonarda, "An Maria," "Stille der Andacht" and "Die Blume der Blumen," three art songs by Luise Reichardt, "Benedictus" from Mass in D by Ethel Smyth, Violet Archer's Three Biblical Songs, Five Spirituals by Margaret Bonds and Missa Patrinae Rerum Domini, a setting of the mass for solo voice by Edith Borroff. The appendices include work lists of the selected composers, IPA transcriptions of the pieces, a chronological listing of composers, and a copy of the program, program notes and lecture from the recital. An extensive bibliography is included.
ISBN: 9780591550726
Keywords: Archer; Bonds; Borroff; Communication and the arts; Edith; England; Ethel; Germany; Isabella; Leonarda; Luise; Margaret; Reichardt; Smyth; Social sciences; Violet

The emergence of a new reality for Quebec Women Composers - Lefebvre, Marie-Thérèse (With a Song in Her Heart: A Celebration of Canadian Women Composers, 1995)

Creating Worlds For Music To Exist: How Women Composers of Electroacoustic Music Make Place For Their Voices - McCartney, Andra (Université York, 1995)

Inventing Images: Constructing and Contesting Gender in Thinking about Electroacoustic Music - McCartney, Andra (Leonardo Music Journal, 1995)
The author explores symbolic imagery in the world of electroacoustic music, as presented in both popular music publications and the language of 14 Canadian women composers. While mainstream discourse uses imagery that emphasizes power and control, these composers use metaphors of painting, dancing, sustenance, addiction, wilderness, meetings, circuitry, curses, locks, boxes, blessings and desire to describe their work. This imagery suggests different ways for artists to think about their interaction with technology.

Whose Playground, Which Games and What Rules?: Women Composers in the Digital Playground - McCartney, Andra (International Composer Music Association, 1995)
Keywords: Pas de lien web

Le Classement des documents musicaux des archives des Ursulines de Québec : démarche archivistique et intérêt musicologique - Vézina-Demers, Micheline (Les Cahiers de l'ARMuQ, 1995)

Violet Archer's Formative Years: A Bibliographical Catalogue of Her Compositions, 1932–43 - Whittle, James (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
This chronological catalogue of Violet Archer's earliest completed compositions, including works written from 1932 to 1943, is based on manuscripts in her possession and on deposit at the University of Calgary Library, as well as published scores and reproductions of manuscripts in the University of Alberta Library and the libraries of the Canadian Music Centre. It provides the date of composition for each work and summarizes the supporting evidence, including dates found on manuscripts, the types of paper used, entries on lists of works compiled by the composer, and dates of first and early performances. Also included are the medium of performance of each work, a list of movements, the source of any text, and the location of scores and recordings.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes